Radial growth-climate correlations and resilience of Robinia pseudoacacia plantations to drought on the Chinese Loess Plateau - Xiaoying Yan; Xiaoying Yan; Xiaoying Yan; Zhongdian Zhang; Zhongdian Zhang; Xiaofei Wu; Xiaofei Wu; Mingbin Huang (Frontiers in Forests and Global Change, 2025)
Robinia pseudoacacia plantations are a key component of vegetation restoration efforts on the Chinese Loess Plateau (CLP) aimed at improving the regional ecological environment. However, a major emerging threat to the sustainable growth of these plantations is drought due to the increasing pressures associated with climate change. To this end, we established standard tree ring width chronologies of R. pseudoacacia at the four sites along a north-south precipitation gradient on the CLP, aiming to determine the relationship between climate and growth as well as quantify tree resilience to drought. Results showed that water availability [precipitation and standardized precipitation evapotranspiration index (SPEI)] and maximum temperature in most seasons were the key climate factors that limited the radial growth of trees in R. pseudoacacia plantations. The relationship between temperature and tree ring width index (RWI) in both regions varied from positive (January, March, and spring) to negative (June) and then to positive (autumn) over time. Spatially, R. pseudoacacia exhibited higher resistance (Rt > 1) to drought and lower recovery (Rc < 1) in the semi-arid region compared to those in semi-humid region under the same drought event (mild, moderate, or severe). The trade-off between drought vulnerability indices indicated the recovery of R. pseudoacacia after drought had a significantly negative correlation with resistance. Resilience of R. pseudoacacia presented a distinct spatiotemporal pattern affected by variations in climate factors (temperature, precipitation and SPEI), site geographical conditions (altitude, longitude, and latitude), and tree characteristics (diameter at breast height (DBH), and RWI for one and two years before a drought event). The effect of site geographical conditions and climate factors, respectively, explained 70.6 and 41.6% of drought resistance and recovery variations. The interaction effects of climate factors and site geographical conditions accounted for 42.8 and 64.3% of the variances in resistance and recovery for R. pseudoacacia, respectively. The results demonstrated the effects of geographical and climatic conditions on the growth of plantation species such as R. pseudoacacia are important considerations that can inform future vegetation restoration efforts to improve the stability and sustainable development of plantation forests on the CLP.